Diagnostic evaluation of magnetic resonance imaging with turbo inversion recovery sequence in head and neck tumors - Sadick, Maliha; Sadick, Haneen; Hörmann, Karl; Düber, Christoph; Diehl, Steffen J. (European archives of oto-rhino-laryngology and head & neck, 2005)
The clinical outcome of patients with head and neck cancer depends on many factors such as tumor size, metastatic involvement and angioarchitecture of the tumor. The correct staging of tumor extension, presence of cervical lymph node metastases and evaluation of vascular infiltration are essential diagnostic steps before treatment. The aim of this study was to evaluate the accuracy of turbo inversion recovery magnitude (TIRM) magnetic resonance imaging (MRI) in the diagnosis of head and neck tumors with special attention to tumor size and tumor spread according to the current TNM classification. TIRM sequence with short T1 relaxation and long TE (echo time) improves imaging contrast because of the increased T1-weighting and the inherent fat suppression. In a prospective clinical study, 32 patients underwent preoperative MRI. Diagnosis was confirmed histologically in all cases. Scanning was performed on a 1.0-T unit applying TIRM as well as T1- and T2-weighted turbo spin echo (TSE) sequences. In all sequences, tumor size was overestimated due to reactive inflammatory changes surrounding the tumor tissue. The least overestimation was documented on TIRM and post-contrast T1 TSE. The highest values of relative tumor signal intensities were obtained in TIRM (3.5±0.9) and T2 TSE (3.5±0.8) followed by post-contrast T1 TSE (1.6±0.7) and pre-contrast T1 TSE (1.2±0.3). Due to the inherent fat suppression, tumor delineation was most obvious in TIRM. In patients with suspected cancer of the head and neck, TIRM should be considered as a standard and a diagnostically relevant sequence in the MRI staging protocol.